A novel TRPM6 variant (c.3179T>A) causing familial hypomagnesemia with secondary hypocalcemia. (5th May 2020) - Lomelino-Pinheiro, Sara; Margarida, Bastos; Lages, Adriana de Sousa
Abstract : Summary: Familial hypomagnesemia with secondary hypocalcemia (FHSH) is a rare autosomal recessive disorder (OMIM# 602014) characterized by profound hypomagnesemia associated with hypocalcemia. It is caused by mutations in the gene encoding transient receptor potential cation channel member 6 (TRPM6). It usually presents with neurological symptoms in the first months of life. We report a case of a neonate presenting with recurrent seizures and severe hypomagnesemia. The genetic testing revealed a novel variant in the TRPM6 gene. The patient has been treated with high-dose magnesium supplementation, remaining asymptomatic and without neurological sequelae until adulthood. Early diagnosis and treatment are important to prevent irreversible neurological damage. Learning points: Loss-of-function mutations of TRPM6 are associated with FHSH. FHSH should be considered in any child with refractory hypocalcemic seizures, especially in cases with serum magnesium levels as low as 0.2 mM. Normocalcemia and relief of clinical symptoms can be assured by administration of high doses of magnesium. Untreated, the disorder may be fatal or may result in irreversible neurological damage.